Digital Storytelling in STEM Mathematics: Communicating Islamic Values through Problem-Based Learning - Siregar, Nur Choiro; Anggrayni, Dewi; Warsito; Gumilar, Aris (Komunika: Journal of Communication Science and Islamic Dakwah, 2025)
This paper conceptualizes Digital Storytelling (DST) in Scince, Technology, Engeneering, Mathematic (STEM) Mathematics as a pedagogical model for strengthening students’ mathematical problem-solving while enabling the communication of Islamic values honesty (ṣidq), responsibility (amānah), cooperation (taʿāwun), and perseverance (ṣabr) within problem-based learning (PBL). The concept paper argues that digital storytelling can function as a “narrative bridge” connecting STEM contexts, mathematical reasoning, and ethical reflection without turning mathematics lessons into moral instruction. The proposed framework positions storytelling as an integrative learning product developed across three cycles: (1) problem framing in authentic STEM situations, (2) modeling and solution development through collaborative mathematical inquiry, and (3) narrative synthesis, where learners produce short digital stories that explain assumptions, justify strategies, and reflect on value-informed decisions and societal impacts. To guide implementation and assessment, the paper outlines design principles for tasks, group roles, and teacher facilitation that promote accountable talk, respectful dialogue, and evidence-based reasoning. It also proposes an assessment approach combining mathematics performance indicators (representation, reasoning, accuracy, and validation) with value-oriented communication indicators (truthfulness in reporting results, responsibility in teamwork, cooperative discourse, and persistence through iterative revision). The paper concludes by highlighting practical implications for curriculum design, classroom assessment rubrics, and teacher professional development in value-integrated STEM education. Future empirical work is recommended to test the model across diverse contexts, compare it with conventional PBL, and examine how narrative features mediate students’ engagement, reasoning quality, and value communication over time.